ANALISIS KEBUTUHAN MODAL KERJA PADA PT.TRIWISNNA DI KABUPATEN KUTAI TIMUR - Catur Kumala dewi 3, Wahid Ari Widodo 1, Titin Ruliana 2 (EKONOMIA, 2020)
ABSTRACT Wahid Ari Widodo. 2018. Analysis of Working Capital Needs at PT. Triwisnna in East Kutai District, under the guidance of Mrs. Titin Ruliana and Mrs. Catur Kumala Dewi.This background is This background is that every company basically needs capital or funds to support the survival of a company and the achievement of its goals. Working capital is a source is essentially directed to finance daily operations in both the short, medium and long trem. the importance of discussing working capital needs because working capital itself is used to carry out company activities. The formulation of the problem is whether the working capital needs at PT. Triwisnna has increased in the period 2014 to 2017. The purpose of this study is in accordance with the previous background, namely to find out and analyze the needs of PT. Triwisnna in the 2014 period until 2017. This research was conducted at PT. Trwisnna residing in East Kutai Regency. Data sources include secondary data. Data collection techniques use interviews with related parties and observations. theoretical basis used in this study is financial management, financial statements and working capital requirements. While the analysis tool uses activity ratios and methods of working capital requirements.